PENDIDIKAN KEWARGANEGARAAN SEBAGAI SARANA PENGUATAN KARAKTER KEWARGANEGARAAN YANG BERORIENTASI PADA LITERASI DIGITAL - Elizabeth Ghozali; Pandapotan Tamba (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The development of the digital era has had a significant impact on the social, cultural, and political life of society, especially the younger generation. This situation requires Civics Education to adapt to remain relevant in shaping students' civic character. This study aims to analyze the role of Civics Education learning in strengthening civic character in the digital era. The research used a qualitative approach with descriptive methods. Data collection techniques were conducted through literature studies and document analysis related to Civics learning. The results indicate that innovative, contextual Civics Education learning utilizing digital technology can improve students' civic character, such as responsibility, tolerance, active participation, and national awareness. Therefore, Civics Education learning needs to be continuously developed by integrating Pancasila values and digital literacy to shape intelligent and character-based citizens.Keywords: Civics Education; Civic Character; Digital Era.